2016
DOI: 10.1111/mec.13589
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and modern colonization of North America by hemlock woolly adelgid, Adelges tsugae (Hemiptera: Adelgidae), an invasive insect from East Asia

Abstract: Hemlock woolly adelgid, Adelges tsugae, is an invasive pest of hemlock trees (Tsuga) in eastern North America. We used 14 microsatellites and mitochondrial COI sequences to assess its worldwide genetic structure and reconstruct its colonization history. The resulting information about its life cycle, biogeography and host specialization could help predict invasion by insect herbivores. We identified eight endemic lineages of hemlock adelgids in central China, western China, Ulleung Island (South Korea), wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 93 publications
(166 reference statements)
1
54
0
Order By: Relevance
“…Within life stages, samples were chosen so that half were infected with S. symbiotica and the remainder were not. All NY samples analyzed had identical microsatellite genotypes, which were also the same as the clonal genotype found throughout eastern United States (Havill et al ., ). This indicated that the absence of S. symbiotica in some A. tsugae individuals is likely not the result of two separate introductions of A. tsugae .…”
Section: Resultsmentioning
confidence: 97%
“…Within life stages, samples were chosen so that half were infected with S. symbiotica and the remainder were not. All NY samples analyzed had identical microsatellite genotypes, which were also the same as the clonal genotype found throughout eastern United States (Havill et al ., ). This indicated that the absence of S. symbiotica in some A. tsugae individuals is likely not the result of two separate introductions of A. tsugae .…”
Section: Resultsmentioning
confidence: 97%
“…Pseudomonas adelgestsugas’ symbionts and Adelges tsugae hosts from five genetically divergent populations [genetic divergence among A. tsugae suggests some populations may be distinct species (Havill et al, 2006, 2016)]. Phylogeny of ‘Ca.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas adelgestsugas’ symbionts (left) was estimated from 16 S rRNA sequences. A. tsugae phylogeny (right) was simplified from Havill et al (2006) and Havill et al (2016), in which all population-level nodes were significantly supported. Sample from Taiwan is new to this study.…”
Section: Resultsmentioning
confidence: 99%
“…Eight distinguishable HWA linages that vary in life cycle, historical biogeography, and host specialization are identified. The lineage of western North America demonstrated higher genetic variation than those in eastern North American, Japan, and Mainland China [20,21]. This suggests the colonization of western North America might have occurred prior to the last glacial period by adelgids directly ancestral to those in southern Japan (perhaps carried by birds, rather than through active dispersal of winged adelgid adults, which are not strong enough to travel across long distances like the Bering land bridge in order to colonize western North America).…”
Section: The Introduction Of Hwa To Eastern North Americamentioning
confidence: 99%
“…This suggests the colonization of western North America might have occurred prior to the last glacial period by adelgids directly ancestral to those in southern Japan (perhaps carried by birds, rather than through active dispersal of winged adelgid adults, which are not strong enough to travel across long distances like the Bering land bridge in order to colonize western North America). In contrast, only one haplotype was identified in all HWA samples in eastern North America (from Massachusetts to West Virginia) and the haplotype was the same as those collected from hemlock ( T. sieboldii ) of Honshu, Japan, indicating that modern invasion of HWA in eastern North America originates in southern Japan [20,21]. This lack of genetic diversity of HWA in eastern North America, and its ability to reproduce asexually may be beneficial for its colonization because HWA will be more likely to establish without the constraint of finding mates in low population density locations [22].…”
Section: The Introduction Of Hwa To Eastern North Americamentioning
confidence: 99%